2014
DOI: 10.3324/haematol.2014.109355
|View full text |Cite
|
Sign up to set email alerts
|

First-line treatment for severe aplastic anemia in children: bone marrow transplantation from a matched family donor versus immunosuppressive therapy

Abstract: ABSTRACThad a high risk of bias due to their study design and were conducted more than 10 years ago and may not be applicable to the standard of care of today.11 Updated evidence to aid treatment decisions in pediatric SAA is, therefore, required.In children, the choice of an appropriate treatment is particularly influenced by the long-term sequelae of the disease and its therapy. Thus, failure-free survival is much more important than survival alone when analyzing the long-term outcomes of children with aplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
78
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(103 citation statements)
references
References 41 publications
15
78
0
10
Order By: Relevance
“…11,16 However, the advantage in failure-free survival for a young patient with a low neutrophil count declines with increasing age 11 as a result of higher mortality after HLA-identical BMT in patients aged 21 to 40 years or older than 40 years.…”
Section: Hla Identical Sibling Transplantation Bmt or Istmentioning
confidence: 99%
See 1 more Smart Citation
“…11,16 However, the advantage in failure-free survival for a young patient with a low neutrophil count declines with increasing age 11 as a result of higher mortality after HLA-identical BMT in patients aged 21 to 40 years or older than 40 years.…”
Section: Hla Identical Sibling Transplantation Bmt or Istmentioning
confidence: 99%
“…26 There is a strong age effect also after IST, as shown in Figure 5, with survival of 82% and 58% for patients younger than 20 or older than 40 years (A.B., EBMT database, unpublished data); this figure outlines survival after first-line IST and includes salvage therapy with a stem cell transplant for nonresponders. Failure-free or transplant-free survival would be clearly inferior 16 and would favor transplantation, but only in younger patients and only when compared with transplants from matched sibling donors. 11 For this reason, current guidelines recommend IST first-line therapy for all patients without a matched sibling donor.…”
Section: Atg1csamentioning
confidence: 99%
“…8 In a recent report from our country (Japan), the causes of treatment failure included GF in 12 patients (5.6%) among 213 children with SAA who received HSCT from an MRD between 1992 and 2009. 9 A report from the National Marrow Donor Program showed that the probability of GF at 28 days and 1 year was 10% and 15%, respectively, in 195 children with AA receiving HSCT from an MUD. 10 The only curative approach to overcome GF is a second allograft for patients failing to engraft after the first transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Transplant-related morbidity and mortality were minimal. Although OS following IST has been very good in the paediatric population (83-94%, Dufour et al, 2015a;Yoshida et al, 2014), quality of life is significantly compromised by the restrictions imposed by prolonged cytopenias as a result of slow count recovery (at least 3-4 months in most cases), with the majority of children only achieving partial remissions (Joeng et al, 2014). Dufour et al (2015b) suggested that a change in the paediatric idiopathic SAA treatment algorithm should be instigated with consideration of upfront MUD BMT, when readily available, in place of IST in those without a matched sibling donor.…”
mentioning
confidence: 99%